ORGANIZATIONAL MANAGEMENT OF ARABIC LANGUAGE LEARNING AT MUSLIM CENDEKIA PRIMARY SCHOOL BATU - Mukhlis, M. Sholahudin; Amalia, Jessica Noer; Ardiansyah, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to analyze the management of organizing Arabic language learning at Muslim Cendekia Primary School Batu. The research method used is a case study, focusing on the management of Arabic teaching and learning activities. Data were obtained through in-depth interviews, participatory observation, and document analysis. The results showed that Muslim Cendekia Primary School Batu has successfully implemented the management of organizing Arabic language learning through three main stages, namely the existence of learning planning, learning implementation, and learning evaluation. In the planning stage, the Arabic curriculum and lesson plans are prepared based on the needs of students and adjusted to the vision and mission of the school as well as teaching materials used to assist teachers. Learning implementation is supported by varied and interactive teaching methods to increase student interest and motivation. Evaluation is conducted periodically and continuously to measure students' progress and achievement. This study concludes that the main challenge in learning Arabic is to increase students' motivation. Recommendations include the use of creative and interactive teaching methods and linking learning materials with students' interests and daily lives.